The role of midkine in health and disease - Neumaier, Emely Elisa; Rothhammer, Veit; Linnerbauer, Mathias (Frontiers in Immunology, 2023)
Midkine (MDK) is a neurotrophic growth factor highly expressed during embryogenesis with important functions related to growth, proliferation, survival, migration, angiogenesis, reproduction, and repair. Recent research has indicated that MDK functions as a key player in autoimmune disorders of the central nervous system (CNS), such as Multiple Sclerosis (MS) and is a promising therapeutic target for the treatment of brain tumors, acute injuries, and other CNS disorders. This review summarizes the modes of action and immunological functions of MDK both in the peripheral immune compartment and in the CNS, particularly in the context of traumatic brain injury, brain tumors, neuroinflammation, and neurodegeneration. Moreover, we discuss the role of MDK as a central mediator of neuro-immune crosstalk, focusing on the interactions between CNS-infiltrating and resident cells such as astrocytes, microglia, and oligodendrocytes. Finally, we highlight the therapeutic potential of MDK and discuss potential therapeutic approaches for the treatment of neurological disorders.